Recovery of Waste-Activated Carbon for Synthesizing High-Efficiency ORR Electrocatalyst - Ziyu Tang; Haowen Li; Xiaojing Jia; Fawei Lin; Kai Li (Energies)
Activated carbon used to adsorb organic pollutants and heavy metals in wastewater is often used to prepare precursor materials to avoid re-polluting the environment. Non-precious metal and heteroatom co-doped electrocatalysts have emerged as promising alternatives to Pt-based catalysts due to their high catalytic activity and remarkable stability. This has greatly developed the ORR process in the field of energy storage, which is restricted due to the high price of Pt-based catalysts. In this study, bamboo shavings were pre-activated to synthesize carbon materials, which were subsequently mixed with an oil phase to simulate “waste-activated carbon”. The results demonstrate that the modified waste-activated carbon exhibits a high specific surface area, a well-developed porous structure, and characteristic element doping, which collectively contribute to the effective construction of active sites. Furthermore, the material displays ORR electrocatalytic performance that surpasses that of commercial Pt/C catalysts. In this study, a high-performance ORR electrocatalyst was successfully synthesized through the retreatment of “waste-activated carbon”. Building on this achievement, this study offers a novel perspective and contributes to advancing research on the resource utilization and sustainable treatment of waste-activated carbon.